Adapting welding method for composite current collector
By welding metal foil on one side, the problems of waste of foil, low welding strength and large overcurrent resistance in the composite fluid-collection welding process are solved, and a more efficient and less wasteful welding effect is achieved.
Patent Information
- Application Number
- CN202411631599.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-02-18
AI Technical Summary
The existing composite fluid-collection welding process has problems such as waste of foil, low welding strength, a large impact on polymer layers, and a large overcurrent resistance of the welded wire.
The method of welding metal foil on one side is adopted, by folding the outside of the white space area of the composite fluid inward, and using an ultrasonic roller welding machine to weld the metal on the pole sheet welding area, the metal on the A and B sides is made The layer is welded to the foil.
It reduces waste of foil, reduces overcurrent resistance, improves welding strength, and optimizes the welding effect of polymer layer.
Smart Images

Figure CN119481078A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of composite current collector production, in particular to a transfer welding method for a composite current collector. Background Art
[0002] Composite current collectors have received widespread attention in the lithium battery industry because they can improve the energy density and safety of batteries while reducing costs to a certain extent. The composite current collectors under existing technologies mainly deposit copper / aluminum metal layers on the surface of PET / PP substrates. The metal layers on both sides do not contact each other, and only form a "sandwich structure" by combining with the polymer base film. Therefore, when applied to lithium-ion batteries, transfer welding is required. By leading out a layer of conventional metal foil from each of the metal layers on both sides, the metal layers on both sides can be conductive, thereby ensuring normal battery performance.
[0003] The existing transfer welding process requires welding metal foil (usually copper / aluminum foil) on both sides of the composite current collector, which results in a large waste of foil. If the composite current collector is folded multiple times before welding, the welding strength is low, and it will also have a certain impact on the subsequent pre-welding and main welding processes. The presence of the polymer layer will greatly affect the welding effect. Moreover, since the metal layer of the composite current collector is relatively thin, this method will cause the overcurrent resistance of the welding wire to be too large, affecting the battery performance.
[0004] Therefore, we propose a transfer welding method for composite current collectors. Summary of the invention
[0005] In order to reduce the waste of transfer metal foil in the current composite current collector transfer welding process, the present invention proposes a welding method that only requires single-side welding of metal foil. Compared with double-sided welding of metal foil, this welding process is more convenient, and compared with transfer welding without using metal foil, the overcurrent resistance is lower.
[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0007] A transfer welding method for a composite current collector comprises the following steps:
[0008] Step S1: folding the outer side of the blank area of the composite current collector inward to form a folded B-side metal layer, thereby obtaining a folded blank area;
[0009] Step S2: Cover the blank area after folding with the transfer metal foil, and perform welding in the electrode welding area to weld the A-side metal layer of the composite current collector, the folded B-side metal layer and the transfer metal foil together to obtain a transfer-welded composite current collector.
[0010] Furthermore, the composite current collector is a composite copper current collector or a composite aluminum current collector.
[0011] Furthermore, the transition metal foil material is aluminum foil corresponding to the composite aluminum current collector, and copper foil corresponding to the composite copper current collector.
[0012] Furthermore, the pole piece is divided into a pole piece coating area and a composite current collector blank area.
[0013] Furthermore, the distance between the electrode welding area and the electrode coating area is ≥8 mm, preferably 8-20 mm.
[0014] Furthermore, the composite current collector should be folded inwards at 3 / 4 of the width of the blank area before welding.
[0015] Furthermore, during the welding, the width of the ultrasonic rolling welding head is 5 mm.
[0016] Furthermore, the length of the transferred metal foil is consistent with the length of the blank area, and the width needs to ensure that the metal foil exceeds the folded edge after welding to meet the needs of subsequent processing.
[0017] Furthermore, in the electrode welding region, the area of the A-side metal layer and the folded B-side metal layer each account for 50%.
[0018] Furthermore, the composite current collector is modified, and the specific process is as follows:
[0019] Step S1: using Ar-O2 plasma technology to modify the surface of the polymer base film to obtain a pre-treated base film; soaking the pre-treated base film in a diethylenetriamine aqueous solution, reacting at 55-65°C for 3-5 minutes, washing and drying to obtain an activated base film;
[0020] Step S2: polyacrylic acid, tannic acid and deionized water are mixed evenly, stirred at 30-40° C. for 1-2 hours, and a composite conductive agent and carbon nanotubes are added and mixed evenly to obtain a conductive slurry;
[0021] Step S3: coating the conductive paste on the upper and lower surfaces of the activated base film respectively, and after curing, forming a conductive layer to obtain a modified polymer base film;
[0022] Step S4: depositing metal layers on the upper and lower surfaces of the modified polymer base film through an atomic deposition process to form an A-side metal layer and a B-side metal layer to obtain a modified composite current collector.
[0023] Furthermore, the polymer base film is one of PP (polypropylene) film, PET (polyethylene terephthalate) film, and PI (polyimide) film.
[0024] Furthermore, in step S1, the process conditions of the Ar-O2 plasma technology are: power 200-300 W, pressure 60-80 Pa, time 4-8 min, and gas mass flow ratio Ar:O2=40 sccm:10 sccm.
[0025] Furthermore, in step S1, the concentration of the diethylenetriamine aqueous solution is 5-10 g / L.
[0026] Furthermore, the conductive paste includes the following components by weight: 2-6 parts of polyacrylic acid, 0.4-1.2 parts of tannic acid, 6-16 parts of composite conductive agent, and 15-25 parts of deionized water.
[0027] Furthermore, the composite conductive agent includes the following components by weight: 1-4 parts of modified graphene oxide and 5-12 parts of modified carbon nanotubes.
[0028] Furthermore, the preparation method of the modified graphene oxide is as follows:
[0029] Ultrasonic dispersion of graphene oxide in deionized water, addition of copper lysine, adjustment of pH to 9-10 with sodium hydroxide, reaction at 70-90° C. for 22-26 h, addition of sodium borohydride as a reducing agent, reflux reaction at 70-90° C. for 1.5-2.5 h, reduction of graphite oxide to graphene, filtration, washing, and drying to obtain modified graphene oxide.
[0030] In the above technical scheme, there are many oxygen-containing groups such as hydroxyl, carboxyl and epoxy groups on the surface of graphene oxide. Copper lysine is used to react with the epoxy groups on the surface of graphene oxide to introduce amino groups. Subsequently, sodium borohydride is used as a reducing agent to effectively reduce the oxygen functional groups (such as carboxyl, hydroxyl, etc.) in the graphene oxide and convert it into graphene. The removal of oxygen functional groups reduces the scattering and defects of electrons in the material, improves the mobility of carriers, and thus enhances the electrical conductivity. At the same time, the copper ions introduced by copper lysine can provide additional electrons as carriers, further improving its conductivity.
[0031] Furthermore, the mass ratio of the graphene oxide, deionized water, copper lysinate and sodium borohydride is 1:(200-300):(2-4):(8-10).
[0032] Furthermore, the preparation method of the modified carbon nanotubes is as follows:
[0033] Step (1): uniformly mixing carbon nanotubes and mixed acid, ultrasonically treating for 5-6 hours, filtering, washing and drying to obtain carboxylated carbon nanotubes; uniformly mixing carboxylated carbon nanotubes, 2-mercaptoethylamine, dichloromethane and triethylamine, adding dicyclohexylcarbodiimide, reacting at 55-65° C. for 22-24 hours to obtain mercaptolated carbon nanotubes;
[0034] Step (2): heating anhydrous ethanol, deionized water, 3-glycidylpropylmethyldimethoxysilane and dimethyldimethoxysilane to 70-80° C., adding dibutyltin dilaurate, reacting for 4-6 hours, then adding vinyldimethylethoxysilane, carrying out end-capping reaction for 3-5 hours, and performing vacuum rotary evaporation to obtain vinyl-terminated epoxy silicone;
[0035] Step (3): The thiol-modified carbon nanotubes, the vinyl-terminated epoxy silicone and the photoinitiator are uniformly mixed, and after ultraviolet irradiation, modified carbon nanotubes are obtained.
[0036] In the above technical scheme, carboxylated carbon nanotubes are prepared by acidifying carbon nanotubes, and carboxyl groups in the carboxylated carbon nanotubes are reacted with amino groups in excess 2-mercaptoethylamine to introduce mercapto groups to obtain mercaptolated carbon nanotubes; 3-glycidylpropylmethyldimethoxysilane, dimethyldimethoxysilane, dimethylethoxyvinylsilane and other raw materials are used to obtain terminal vinyl epoxy silicone through a hydrolysis condensation method, which not only has a good viscosity-increasing effect, but also can improve the dispersibility of the filler and enhance the interface compatibility; finally, the mercapto-ene click reaction between the mercaptolated carbon nanotubes and the terminal vinyl epoxy silicone is carried out to obtain modified carbon nanotubes containing epoxy silicone structures.
[0037] Furthermore, in the step (1), the solid-liquid ratio of the carbon nanotubes to the mixed acid is 1:(120-150) g / mL, and the mixed acid is prepared by concentrating sulfuric acid and concentrating nitric acid in a volume ratio of 3:1.
[0038] Furthermore, in the step (1), the mass ratio of carboxylated carbon nanotubes, 2-mercaptoethylamine, dichloromethane and triethylamine is 1:(2-4):(1-2):(0.1-0.3).
[0039] Furthermore, in the step (1), the mass of dicyclohexylcarbodiimide is 15-20 times the mass of the carboxylated carbon nanotubes.
[0040] Furthermore, in step (2), the vinyl-terminated epoxy silicone comprises the following components by weight: 20-25 parts of anhydrous ethanol, 4-6 parts of deionized water, 10-12 parts of 3-glycidylpropylmethyldimethoxysilane, 11-13 parts of dimethyldimethoxysilane, 12-14 parts of vinyldimethylethoxysilane, and 0.02-0.05 parts of dibutyltin dilaurate.
[0041] Furthermore, in the step (2), the mass ratio of the thiolated carbon nanotubes, the vinyl-terminated epoxy silicone and the photoinitiator is 1:(2-3):(0.3-0.5).
[0042] Furthermore, the photoinitiator is 2-hydroxy-2-methylpropiophenone.
[0043] Furthermore, the process conditions of the ultraviolet irradiation are: irradiation wavelength 360-400nm, irradiation time 0.5-2.0h, irradiation intensity 20-35mW / cm 2 .
[0044] Furthermore, in step S4, the atomic deposition process is one of evaporation, magnetron sputtering, and electroplating.
[0045] Furthermore, the curing process conditions are: curing at 80-120° C. for 12-24 hours.
[0046] Furthermore, the thickness of the conductive layer is 0.5-2.0 μm.
[0047] Compared with the prior art, the present invention has the following beneficial effects:
[0048] 1. A transfer welding method for a composite current collector of the present invention uses only a single-sided metal foil to conduct the metal layer of the A / B side of the composite current collector, thereby reducing the waste of foil and being superior to a transfer welding solution that does not use metal foil in terms of resistance performance.
[0049] 2. A transfer welding method for a composite current collector of the present invention adopts Ar-O2 plasma technology and uses diethylenetriamine (DETA) as a modifier to perform surface activation grafting modification on a polymer base film, introduce -NH2 functional groups, obtain an activated base film, and improve the hydrophilicity of the molecular base film to increase surface roughness and active sites while maintaining good timeliness; the use of copper lysine not only provides copper ions, but also can react with graphene oxide through its amino group, and then converts the graphene oxide into graphene through sodium borohydride to improve its electrical conductivity and obtain modified graphene; mercapto-ene click reaction is carried out between thiol-modified carbon nanotubes and terminal vinyl epoxy silicone to obtain modified carbon nanotubes containing epoxy silicone structure, which can form a chemical bond with the modified graphene, thereby improving the conductivity, mechanical properties and thermal stability of the composite conductive agent, which not only enhances the electronic conduction path and promotes the migration of carriers, but also improves the interface bonding and enhances the strength and toughness of the material. In addition, due to the good compatibility between modified carbon nanotubes and graphene, agglomeration can be avoided, ensuring the uniform dispersion of the material in the polymer matrix, thereby greatly improving the overall performance.
[0050] 3. A transfer welding method for a composite current collector of the present invention controls the ratio of modified graphene to modified carbon nanotubes in the composite conductive agent so that unreacted epoxy groups are retained in the composite conductive agent and react with the activated base film, thereby further enhancing the bonding between the conductive layer and the polymer base film. At the same time, the composite conductive agent has a high surface area and good mechanical strength, which can provide good support for the subsequent metal deposition process. By introducing a conductive layer between the polymer base film and the metal layer, not only can the bonding force between the metal layer and the polymer base film be effectively improved, but also the current transmission path can be optimized, thereby improving the conductive properties of the composite current collector. BRIEF DESCRIPTION OF THE DRAWINGS
[0051] The accompanying drawings are used to provide a further understanding of the present invention and constitute a part of the specification. Together with the embodiments of the present invention, they are used to explain the present invention and do not constitute a limitation of the present invention. In the accompanying drawings:
[0052] Figure 1 is a schematic diagram of the structure of the composite current collector before transfer welding in Example 1 of the present invention;
[0053] Figure 2 is a schematic diagram of the blank area after folding in Example 1 of the present invention;
[0054] Figure 3 1 is a schematic diagram of the structure in which the blank area is covered with the transition metal foil in Embodiment 1 of the present invention;
[0055] Figure 4 is a schematic diagram of the structure of the composite current collector after transfer welding in Example 1 of the present invention;
[0056] In the figure: 1 is the electrode coating area, 2 is the blank area of the composite current collector, and 3 is the transition metal foil. DETAILED DESCRIPTION
[0057] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0058] It should be noted that there is no special restriction on the purchasing manufacturers of all the raw materials involved in the present invention, and illustratively include: polymer base film: PP film, with a thickness of 5 μm, which can be purchased from Dongguan Zhonglian Electronic Materials Co., Ltd.; composite current collector: composite aluminum current collector, which can be purchased from Shenzhen Kejing Zhida Technology Co., Ltd.; transfer metal foil: aluminum foil, with a thickness of 12 μm, brand H18-1100, which can be purchased from Shenzhen Honglei Metal Materials Co., Ltd.; polyacrylic acid: solid content of 25%, which can be purchased from Wuhan Prov Biotechnology Co., Ltd.; graphene oxide: model DN-20DY, which can be purchased from Zhejiang Zhiti Nano Micro New Materials Co., Ltd.; carbon nanotubes: model NACODC8, which can be purchased from Jiaxing Naco New Materials Co., Ltd.
[0059] In the following examples and comparative examples, 1 part is equal to 10 g.
[0060] Embodiment 1: A transfer welding method for a composite current collector comprises the following steps:
[0061] Step S1: Fold the outer side of the composite current collector blank area 2 inward along the dotted line to form a folded B-side metal layer, and obtain a folded blank area, such as Figure 2 As shown;
[0062] Step S2: Cover the transfer metal foil 3 on the folded blank area, such as Figure 3 As shown, an ultrasonic roll welder is used to weld the electrode welding area, so that the A-side metal layer of the composite current collector, the folded B-side metal layer and the transfer metal foil are welded together to obtain a transfer-welded composite current collector, such as Figure 4 shown.
[0063] Embodiment 2: A transfer welding method for a composite current collector comprises the following steps:
[0064] Step S1: folding the outer side of the blank area of the composite current collector inward to form a folded B-side metal layer, thereby obtaining a folded blank area;
[0065] Step S2: Covering the blank area after folding with a transfer metal foil, and using an ultrasonic roll welder to weld the electrode welding area, so that the A-side metal layer of the composite current collector, the folded B-side metal layer and the transfer metal foil are welded together to obtain a transfer-welded composite current collector;
[0066] The composite current collector is modified, and the specific process is as follows:
[0067] Step S1: using Ar-O2 plasma technology to modify the surface of the polymer base film (power 200W, pressure 60Pa, time 8min, gas mass flow ratio Ar:O2=40sccm:10sccm) to obtain a pre-treated base film; soaking the pre-treated base film in a 5g / L diethylenetriamine aqueous solution, reacting at 55°C for 5min, washing and drying to obtain an activated base film;
[0068] Step S2: 2 parts of polyacrylic acid, 0.4 parts of tannic acid and 15 parts of deionized water are mixed evenly, stirred at 30° C. for 1 hour, and 6 parts of a composite conductive agent (formed by 1 part of modified graphene oxide and 5 parts of modified carbon nanotubes) are added and mixed evenly to obtain a conductive slurry;
[0069] Step S3: applying the conductive paste to the upper and lower surfaces of the activated base film respectively, and after curing (curing at 80° C. for 24 hours), a conductive layer is formed to obtain a modified polymer base film;
[0070] Step S4: depositing a metal copper layer on the upper and lower surfaces of the modified polymer base film by evaporation to form an A-side metal layer and a B-side metal layer to obtain a modified composite current collector;
[0071] The preparation method of modified graphene oxide is as follows:
[0072] 1 part of graphene oxide was ultrasonically dispersed in 200 parts of deionized water, 2 parts of copper lysine were added, pH=9 was adjusted with sodium hydroxide, the reaction was carried out at 70°C for 22 hours, 8 parts of sodium borohydride were added as a reducing agent, the reaction was carried out at 70°C for 1.5 hours, the graphite oxide was reduced to graphene, and the modified graphene oxide was obtained after filtering, washing and drying;
[0073] The preparation method of modified carbon nanotubes is as follows:
[0074] Step (1): 5 parts of carbon nanotubes and 600 mL of mixed acid (prepared with concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 3:1) are mixed evenly, ultrasonically treated for 5 hours, filtered, washed, and dried to obtain carboxylated carbon nanotubes; 5 parts of carboxylated carbon nanotubes, 10 parts of 2-mercaptoethylamine, 5 parts of dichloromethane, and 0.5 parts of triethylamine are mixed evenly, 75 parts of dicyclohexylcarbodiimide are added, and the mixture is reacted at 55° C. for 22 hours to obtain mercaptolated carbon nanotubes;
[0075] Step (2): 20 parts of anhydrous ethanol, 4 parts of deionized water, 10 parts of 3-glycidylpropylmethyldimethoxysilane and 11 parts of dimethyldimethoxysilane are heated to 70°C, 0.02 parts of dibutyltin dilaurate are added, and the reaction is carried out for 4 hours, and then 12 parts of vinyldimethylethoxysilane are added, and the end-capping reaction is carried out for 3 hours, and vacuum rotary evaporation is performed to obtain a vinyl-terminated epoxy silicone;
[0076] Step (3): 5 parts of thiolated carbon nanotubes, 10 parts of vinyl-terminated epoxy silicone and 1.5 parts of photoinitiator were mixed evenly and irradiated with ultraviolet light (irradiation wavelength 360 nm, irradiation time 0.5 h, irradiation intensity 35 mW / cm 2 ) to obtain modified carbon nanotubes.
[0077] Embodiment 3: A transfer welding method for a composite current collector, comprising the following steps:
[0078] Step S1: folding the outer side of the blank area of the composite current collector inward to form a folded B-side metal layer, thereby obtaining a folded blank area;
[0079] Step S2: Covering the blank area after folding with a transfer metal foil, and using an ultrasonic roll welder to weld the electrode welding area, so that the A-side metal layer of the composite current collector, the folded B-side metal layer and the transfer metal foil are welded together to obtain a transfer-welded composite current collector;
[0080] The composite current collector is modified, and the specific process is as follows:
[0081] Step S1: using Ar-O2 plasma technology to modify the surface of the polymer base film (power 300W, pressure 80Pa, time 4min, gas mass flow ratio Ar:O2=40sccm:10sccm) to obtain a pre-treated base film; soaking the pre-treated base film in a 10g / L diethylenetriamine aqueous solution, reacting at 65°C for 3min, washing and drying to obtain an activated base film;
[0082] Step S2: 6 parts of polyacrylic acid, 1.2 parts of tannic acid and 25 parts of deionized water are mixed evenly, stirred at 40° C. for 2 hours, and 16 parts of a composite conductive agent (formed by 4 parts of modified graphene oxide and 12 parts of modified carbon nanotubes) are added and mixed evenly to obtain a conductive slurry;
[0083] Step S3: applying the conductive paste to the upper and lower surfaces of the activated base film respectively, and after curing (curing at 120° C. for 12 hours), a conductive layer is formed to obtain a modified polymer base film;
[0084] Step S4: depositing a metal copper layer on the upper and lower surfaces of the modified polymer base film by evaporation to form an A-side metal layer and a B-side metal layer to obtain a modified composite current collector;
[0085] The preparation method of modified graphene oxide is as follows:
[0086] 4 parts of graphene oxide were ultrasonically dispersed in 1200 parts of deionized water, 16 parts of copper lysine were added, pH=10 was adjusted with sodium hydroxide, the reaction was carried out at 90°C for 26 hours, 40 parts of sodium borohydride were added as a reducing agent, the reaction was carried out at 90°C for 2.5 hours, the graphite oxide was reduced to graphene, and the modified graphene oxide was obtained after filtering, washing and drying;
[0087] The preparation method of modified carbon nanotubes is as follows:
[0088] Step (1): 12 parts of carbon nanotubes and 1800 mL of mixed acid (prepared with concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 3:1) are mixed evenly, ultrasonically treated for 6 hours, filtered, washed, and dried to obtain carboxylated carbon nanotubes; 12 parts of carboxylated carbon nanotubes, 48 parts of 2-mercaptoethylamine, 24 parts of dichloromethane, and 3.6 parts of triethylamine are mixed evenly, dicyclohexylcarbodiimide is added, and the mixture is reacted at 65° C. for 24 hours to obtain mercaptolated carbon nanotubes;
[0089] Step (2): 25 parts of anhydrous ethanol, 6 parts of deionized water, 12 parts of 3-glycidylpropylmethyldimethoxysilane and 13 parts of dimethyldimethoxysilane are heated to 80°C, 0.05 parts of dibutyltin dilaurate are added, and the reaction is carried out for 6 hours, and then 14 parts of vinyldimethylethoxysilane are added, and the end-capping reaction is carried out for 5 hours, and vacuum rotary evaporation is performed to obtain a vinyl-terminated epoxy silicone;
[0090] Step (3): 12 parts of thiolated carbon nanotubes, 36 parts of vinyl-terminated epoxy silicone and 6 parts of photoinitiator were mixed evenly and irradiated with ultraviolet light (irradiation wavelength 400nm, irradiation time 2.0h, irradiation intensity 20mW / cm 2 ) to obtain modified carbon nanotubes.
[0091] Comparative Example 1: A transfer welding method for a composite current collector, comprising the following steps:
[0092] Covering the transfer metal foil on the upper surface or the lower surface of the blank area of the composite current collector respectively, and using an ultrasonic roll welder to weld the metal layer of the composite current collector and the transfer metal foil together in the electrode welding area to obtain a transfer-welded composite current collector;
[0093] Compared with Example 1, the transition process of Comparative Example 1 is to weld the transition metal foil on one side of the composite current collector.
[0094] Comparative Example 2: A transfer welding method for a composite current collector, comprising the following steps:
[0095] Compared with Example 1, in Comparative Example 2, no transition metal foil is used, but the blank area of the composite current collector is folded twice to form a three-layer folded structure, which is then welded to achieve conduction of the metal conductor layers on both sides of the composite current collector.
[0096] Comparative Example 3: A transfer welding method for a composite current collector, comprising the following steps:
[0097] Compared with Example 2, in Comparative Example 3, the modified carbon nanotubes are replaced with carbon nanotubes of the same mass, and the other steps are the same as those of Example 2.
[0098] Comparative Example 4: A transfer welding method for a composite current collector, comprising the following steps:
[0099] Compared with Example 2, the composite conductive agent of Comparative Example 4 is compounded by 5 parts of modified graphene oxide and 1 part of modified carbon nanotubes, and the other steps are the same as those of Example 2.
[0100] Experiment: Overcurrent resistance test: Take the composite current collectors after transfer welding obtained in Examples 1-3 and Comparative Examples 1-4, and perform overcurrent resistance tests on different welding areas.
[0101] Welding wire overcurrent resistance test method: Use Hioki RM3545 microresistance meter for testing. The probe clamps both sides of the welding wire. One side is a single-layer current collector and the other side is a double-layer foil. The sample width is 30 mm. The test results are shown in Table 1.
[0102] Table 1 Overcurrent resistance of welding area in Examples 1-3 and Comparative Examples 1-4
[0103]
[0104] According to the data in the above table, we can clearly draw the following conclusions:
[0105] 1. Compared with Example 1, the overcurrent resistance of Comparative Example 1 is reduced, while the overcurrent resistance of Comparative Example 2 is increased, which shows that the present application uses single-sided aluminum foil as the transition metal foil for welding. Although the overcurrent resistance is improved compared to the case of using double-sided aluminum foil, it is significantly lower than the overcurrent resistance without using aluminum foil. Therefore, this welding scheme effectively reduces the excessive use of aluminum foil while ensuring that the overcurrent resistance of the welding wire after welding meets the requirements.
[0106] 2. Compared with Examples 2-3, the overcurrent resistance of Comparative Example 3 increases. It can be seen that compared with the unmodified carbon nanotubes, the carbon nanotubes prepared in the present invention have epoxy groups, which can play a synergistic role with the modified graphene, thereby showing more superior conductive properties.
[0107] 3. Compared with Examples 2-3, the overcurrent resistance of Comparative Example 4 increases, indicating that the composite conductive agent prepared by the present invention is affected by the composition ratio. By selecting a mass ratio within the range, the prepared material has excellent conductive properties.
[0108] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process method article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process method article or device.
[0109] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered exemplary and non-limiting in all respects, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations falling within the meaning and scope of the equivalent elements of the claims be included in the invention. Any reference numeral in a claim should not be considered as limiting the claim to which it relates.
Claims
1. A transfer welding method for a composite current collector, characterized in that: The steps include: Step S1: folding the outer side of the composite current collector blank area (2) inward to form a folded B-side metal layer, thereby obtaining a folded blank area; Step S2: Cover the transition metal foil (3) on the blank area after folding, and perform welding in the electrode welding area, so that the A-side metal layer of the composite current collector, the folded B-side metal layer and the transition metal foil are welded together to obtain a composite current collector after transfer welding.
2. A transfer welding method for a composite current collector according to claim 1, characterized in that: The composite current collector is one of a composite copper current collector and a composite aluminum current collector.
3. A transfer welding method for a composite current collector according to claim 2, characterized in that: The transition metal foil material is aluminum foil corresponding to the composite aluminum current collector, and copper foil corresponding to the composite copper current collector.
4. The transfer welding method of a composite current collector according to claim 1, characterized in that: The distance between the pole piece welding area and the pole piece coating area (1) is 8-20 mm.
5. The transfer welding method of a composite current collector according to claim 1, characterized in that: Before welding, the composite current collector should be folded inwards at 3 / 4 of the width of the blank area.
6. A transfer welding method for a composite current collector according to claim 1, characterized in that: In the electrode welding area, the area of the A-side metal layer and the folded B-side metal layer each accounts for 50%.
7. The transfer welding method of a composite current collector according to claim 1, characterized in that: The composite current collector is modified, and the specific process is as follows: Step S1: using Ar-O2 plasma technology to modify the surface of the polymer base film to obtain a pre-treated base film; soaking the pre-treated base film in a diethylenetriamine aqueous solution, reacting at 55-65°C for 3-5 minutes, washing and drying to obtain an activated base film; Step S2: Mix polyacrylic acid, tannic acid and deionized water evenly, stir at 30-40° C. for 1-2 hours, add a composite conductive agent and mix evenly to obtain a conductive slurry; Step S3: coating the conductive paste on the upper and lower surfaces of the activated base film respectively, and after curing, forming a conductive layer to obtain a modified polymer base film; Step S4: depositing metal layers on the upper and lower surfaces of the modified polymer base film through an atomic deposition process to form an A-side metal layer and a B-side metal layer to obtain a modified composite current collector.
8. A transfer welding method for a composite current collector according to claim 7, characterized in that: The composite conductive agent comprises the following components by weight: 1-4 parts of modified graphene oxide and 5-12 parts of modified carbon nanotubes.
9. A transfer welding method for a composite current collector according to claim 8, characterized in that: The preparation method of the modified graphene oxide is as follows: Ultrasonic dispersion of graphene oxide in deionized water, addition of copper lysine, adjustment of pH to 9-10 with sodium hydroxide, reaction at 70-90° C. for 22-26 h, addition of sodium borohydride as a reducing agent, reflux reaction at 70-90° C. for 1.5-2.5 h, reduction of graphite oxide to graphene, filtration, washing, and drying to obtain modified graphene oxide.
10. A transfer welding method for a composite current collector according to claim 8, characterized in that: The preparation method of the modified carbon nanotubes is as follows: Step (1): uniformly mixing carbon nanotubes and mixed acid, ultrasonically treating for 5-6 hours, filtering, washing and drying to obtain carboxylated carbon nanotubes; uniformly mixing carboxylated carbon nanotubes, 2-mercaptoethylamine, dichloromethane and triethylamine, adding dicyclohexylcarbodiimide, reacting at 55-65° C. for 22-24 hours to obtain mercaptolated carbon nanotubes; Step (2): heating anhydrous ethanol, deionized water, 3-glycidylpropylmethyldimethoxysilane and dimethyldimethoxysilane to 70-80° C., adding dibutyltin dilaurate, reacting for 4-6 hours, then adding vinyldimethylethoxysilane, carrying out end-capping reaction for 3-5 hours, and performing vacuum rotary evaporation to obtain vinyl-terminated epoxy silicone; Step (3): The thiol-modified carbon nanotubes, the vinyl-terminated epoxy silicone and the photoinitiator are uniformly mixed, and after ultraviolet irradiation, modified carbon nanotubes are obtained.
